“I Have No Capacities That Can Help Me”: Young Asylum Seekers in Norway and Serbia – Flight as Disturbance of Developmental Processes - Varvin, Sverre; Vladisavljević, Ivana; Jović, Vladimir; Sagbakken, Mette (Frontiers in Psychology, 2022)
Most studies on refugee populations are organized around trauma-related issues and focus on explanations of pathological factors. Few studies are anchored in general developmental psychology with the aim of exploring normal age-specific developmental tasks and how the special circumstances associated with forced migration can influence how developmental tasks are negotiated. This study is part of a larger mixed method study seeking to identify resilience promoting and resilience inhibiting factors, on individual and contextual levels, among asylum seekers and refugees on the move (passing through Serbia) and settled in reception centers in Norway. A strategic sample of 20 adolescent and young adult refugees/asylum seekers during flight in Serbia (10) and after arrival in Norway (10) were chosen from a sample of 178 refugees interviewed in depth in Serbia and at receptions centers in Norway. The sample reflects the focus of this paper, as it seeks to explore adolescent and young adult refugees/asylum seekers’ psychological and social needs and resources during flight and after arrival to the host country, including how developmental tasks are negotiated. Through qualitative analysis experiences connected to the developmental changes the participants have experienced before, during and after flight are contextualized. Relation to self, to their families, to their situation as adolescents or young adults in a situation with great degree of unpredictability is presented in the light of relevant theory and findings from similar refugee studies. All participants have fled from dangerous and intolerable situations in their home countries. They describe extreme dangers during flight in contexts that are unpredictable where they feel lonely and unsupported. Most have unmet psychosocial needs, and they describe that there has been little support and help for their mental health both during flight and after arrival in Norway. Suggestion for interventions and resilience promoting actions are given based on findings in the study.